PENGARUH HARGA MATERIAL BAHAN BAKU PLAT TERHADAP PELAYANAN JASA KONSTRUKSI SIPIL BAJA TANKI MINYAK KELAPA SAWIT CV. SAMACO DI SIDOARJO - Januar Pratama; Sofyan Lazuardi (CV ODIS, 2022)
With this is a CV. Samaco also conducts price games to offer the best price to employers not to give expensive prices, the increasing price of steel plate raw materials during the Covid-19 pandemic also affects the company's activities. Passionate work to innovate, as well as the development of sophisticated technology can be effective in working and increase future business opportunities. CV. Samaco aims to improve the best service to consumers to the maximum, support with a good work environment and work ethic in advancing to technology. The raw materials used by steel plates as a working medium, from the bookers of various kinds requested there are those who use steel plates and steinless plates of varying sizes. CV. Samaco will provide satisfactory work results to the Owner who carries out the work so that in the future it will be invited to cooperate again.